Engineering oxygen nanobubbles for the effective reversal of hypoxia. (12th November 2018) - Khan, Muhammad Saad; Hwang, Jangsun; Seo, Youngmin; Shin, Kyusoon; Lee, Kyungwoo; Park, Chanhwi; Choi, Yonghyun; Hong, Jong Wook; Choi, Jonghoon
Abstract: Hypoxia, which results from an inadequate supply of oxygen, is a major cause of concern in cancer therapy as it is associated with a reduction in the effectiveness of chemotherapy and radiotherapy in cancer treatment. Overexpression and stabilization of hypoxia-inducible factor 1α (HIF-1α) protein in tumours, due to hypoxia, results in poor prognosis and increased patient mortality. To increase oxygen tension in hypoxic areas, micro- and nanobubbles have been investigated by various researchers. In the present research, lipid-shelled oxygen nanobubbles (ONBs) were synthesized through a sonication method to reverse hypoxic conditions created in a custom-made hypoxic chamber. Release of oxygen gas from ONBs in deoxygenated water was evaluated by measuring dissolved oxygen. Hypoxic conditions were evaluated by performing in vitro experiments on MDA-MB231 breast cancer cells through the expression of HIF-1α and the fluorescence of image-iT™ hypoxia reagent. The results indicated the degradation of HIF-1α after the introduction of ONBs. We propose that ONBs are successful in reversing hypoxia, downregulating HIF-1α, and improving cellular conditions, leading to further medical applications.